1992 annual report - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 1992)
The Central Plains Experimental Range Shortgrass Steppe long term ecological research project (BSR-9011659 LTER) had a successful year in 1991-92. We have continued to collect data regarding long term patterns in ecosystem structure and function, while initiating important new studies to further our understanding of the shortgrass steppe. The project produced 20 papers in refereed journals during the last 2 years (1990 and 1991). We supported a large number of graduate, undergraduate, and high school students for research at the site. Scientists from our project are involved in LTER network activities, through comparative modeling studies, database management, and development of new cross-site experiments. We provide a summary of the new activities and products from our site during 1991-1992, and our plans for 1992-93. A more detailed description of our scientific activities, organized by core area is included.
Progress report
SGS-LTER 1992 annual report
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: shortgrass steppe; Central Plains Experimental Range; Pawnee National Grassland; grassland ecology; long term ecological research